Pathogenicity, fungicide sensitivity and morphology of South African isolates of Ramulispora herpotrichoides - Robbertse, Barbara (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc. Agric.) -- University of Stellenbosch, 1994.